Troubleshooting and improving an existing robot used in verification test - Skaug, Emil (My University, 2026)
Reliable verification of radar measurements is essential for ensuring safe operation in industrial environments. At Emerson Rosemount Tank Radar AB, a wireless measuring robot is used inside pipes to perform factory acceptance tests of a radar transmitter. However, recurring stoppages and poor communication with the robot have delayed the verification process. This project investigates the root causes of these issues and the connection to the communication system. To investigate and evaluate potential improvements, a test script was developed to log registers and communication response times of the robot. The results showed that relocating the Bluetooth transmitter improved communication stability, and several hypotheses regarding the unknown stoppages could be ruled out. In addition, the existing battery solution for the wireless robot is temporary, therefore three alternative concepts were developed and evaluated against technical and usability requirements. To ensure the robot’s long-term operation, a spare parts analysis was conducted, revealing risks related to discontinued electronic components and wear parts. The outcome of the project is a more stable Bluetooth connection and improved long-term maintainability of the measuring robot, helping to ensure its continued use in factory acceptance testing.